Zbiorowiska roślinności łąkowej z klasy Molinio-Arrhenatheretea w dolinie Ochoży - Danuta Urban; Antoni Grzywna (Agronomy Science, 2003)
The paper presents results of the study on meadows of Molinio-Arrhenatheretea on grasslands in the Ochoża Valley. The aim of the paper was to determine the phyto-sociological differentiation of plant communities depending on the water and soil conditions and the use of the land. The studies carried out will be a starting point to determine the direction of succession of the plant communities. Based on 87 phytosociological records made by the modified Braun-Blanquets method, 8 associations and 6 plant communities of unknown phytosociological position were differentiated. On the basis of the studies it was found that the largest area in the Ochoża Valley is occupied by the Festuca rubra-Poa pratensis plant community and Deschampsietum caespitosae, Holcetum lanati and Alopecuretum pratensis complexes. As a result of abandoned use of some fragments of the valley as meadows, the meadow sward exhibits a substantially lower content of species from the Molinio-Arrhenatheretea class. Numerous stretches of sward were dominated by Urtica dioica, Anthriscus sylvestris and Cardminopsis arenosa. Among the species that are rare and protected by law, the 800 specimens of Polemonium caeruleum, growing in the meadows of the Ochoża Valley, are worthy of special attention.